Synchrotron based operando surface X‐ray scattering study towards structure–activity relationships of model electrocatalysts. Issue 5 (29th April 2016) - Goryachev, Andrey; Carlà, Francesco; Drnec, Jakub; Onderwaater, Willem G.; Felici, Roberto; Krause, Philipp P. T.; Wonders, Ad H.; Hensen, Emiel J. M.; Hofmann, Jan P.
Abstract: A novel combination of Surface X‐ray Scattering techniques (SXS), i. e. GISAXS (Grazing‐Incidence Small‐Angle X‐Ray Scattering), XRR (X‐Ray Reflectivity) and SXRD (Surface X‐Ray Diffraction) alongside with simultaneous detection of gaseous products by OLEMS (On‐Line Electrochemical Mass Spectrometry) has been applied to study under operando conditions structure‐activity relationships of a Pt model electrocatalyst. The SXS‐OLEMS combination is able to follow dynamic changes in surface morphology and crystallography during water electrolysis. To showcase the combined SXS‐OLEMS setup for operando studies of electrode transformations, H2 and O2 evolution reactions (HER and OER) on a Pt model electrocatalyst and their dependence on type and degree of surface roughening have been investigated. Abstract : A combined Surface X‐ray Scattering (SXS) – On‐Line‐Electrochemical Mass Spectrometry (OLEMS) setup is presented to study structure‐activity relationships of electrocatalytic surfaces under operando electrochemical conditions. The approach is introduced on Pt(111) as a single crystal model electrode investigating hydrogen and oxygen (HER and OER) evolution reactions.